Literasi Digital untuk menumbuhkan Jiwa Wirausaha Muda pada Peserta Didik SMK Bina Insan Tangerang - Maria Ulfa; Sahid Alfatah; Afif Fauzan Baharianto; Diana Elsa Fitri; Muhammad Imam Al- Muttaqien; Muhamad Yuladi Firichal; Riki Hidayat (Prodi Ekonomi Syariah Universitas Pamulang, 2024)
This community service initiative aims to socialize and provide an understanding of digital literacy to foster an entrepreneurial spirit from an early age in the community. In the continuously evolving digital era, digital literacy has become a key skill necessary not only to adapt but also to thrive and succeed in various fields of life, including the entrepreneurial world. Young entrepreneurs, with their courage and creativity, have the potential to transform the global economic landscape. However, to achieve success in an increasingly interconnected digital environment, they need to be equipped with adequate knowledge and skills in digital literacy. Digital literacy encompasses understanding how to use digital technology effectively and responsibly, as well as the ability to interpret information obtained from various digital platforms. This includes skills such as internet usage, data analysis, digital security, and the ability to communicate effectively through social media and other online platforms. For young entrepreneurs, digital literacy is not just about technical skills but also about how they can leverage technology to create and grow their businesses. In a rapidly changing world, the ability to harness technology and identify new opportunities is key to surviving and thriving. The team from the Sharia Economics Study Program at Pamulang University has successfully conducted a socialization event titled